A new species of Bryconamericus (Characidae: Stevardiinae: Diapomini) from the upper rio Paraná basin, Brazil - Jerep,Fernando C. (2017)
ABSTRACT Bryconamericus is the most diverse genus within Stevardiinae, comprising 61 valid species distributed in Cis- and Trans-Andean basins from Panama in Central America to northern Argentina in South America. Three species are known from the upper rio Paraná basin: B. exodon, B. iheringii, and B. turiuba. Herein we describe a new species of Bryconamericus from the upper rio Paraná basin inhabiting tributaries of Ivaí, Piquiri, and Tibagi basins, Paraná State, Brazil. The new species differs from its congeners by the presence of unaligned teeth in the outer tooth row of the premaxilla; a single, vertical, dorsally expanded and rounded humeral spot; 36-39 pored scales in the longitudinal series; body depth 31.6-37.9% SL; anal-fin base length 24.8-30.1% SL; number of branched anal-fin rays 19-22, and bony hooks on pelvic- and anal-fin rays of sexually dimorphic males. The new species is syntopic with other Stervadiinae in the upper rio Paraná basin such as B. iheringii, B. turiuba, Piabarchus stramineus, and Piabina argentea.